Perlindungan Konsumen terhadap Pelaku Usaha Jasa Pangkas Rambut yang Wanprestasi - Ardina Khoirun Nisa; Defriza, Rita (El-Ahli : Jurnal Hukum Keluarga Islam, 2023)
Consumer protection is a set of legal rules made to provide protection to consumers, so that there is a balance between service businesses and consumers. In the case of business actors who offer barber services, of course, sometimes things do not meet consumer expectations, for example, mistakes in cutting and tidying hair, injuries resulting from negligence of barbering services that cause losses to customers or consumers. This situation provides an understanding of the need for consumer protection as a party that is often harmed. Fair protection and equal treatment before the law has been contained in the law. The problem is regarding how to arrange compensation by barber service business actors to consumers as a result of errors in cutting hair and causing injuries during the shaving process and how is the implementation of compensation by barber service business actors to consumers due to errors in cutting hair and incurring injuries during the process shaving. The method used is empirical research by looking at social phenomena in society based on existing data in the field.